2016
DOI: 10.1016/j.ijsu.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Validation of DWI in assessment of radiotreated bone metastases in elderly patients

Abstract: Bone metastases are commonly observed in oncologic patients with advanced disease. These metastases are considered the main cause of neoplastic pain, with more than half of oncologic patients experiencing neoplastic pain during the course of the disease due to bone involvement. Lung, breast, and prostate cancers are the primary causes of bone metastases. Magnetic resonance imaging (MRI), especially diffusion weighted imaging (DWI) sequences, is the focus of our research, as it has been proven to be an optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…However, the combination of clinical breast examination, mammography and US has not sufficiently sensitive in high-risk women, as demonstrated by many series (11,25) and consequently, has a minor role in patients with hereditary predisposition to the disease. In fact, this diagnostic combination has demonstrated a sensitivity of 64% in our BRCA mutation carriers and a lower sensitivity than its estimated (83%) for detection in the general population, as well known from many studies (12,16,25,32,33). Furthermore, the higher sensitivity of MRI in lesion detection is consistent if considering its high capability to detect potential axillary nodal involvement.…”
Section: Discussionmentioning
confidence: 81%
“…However, the combination of clinical breast examination, mammography and US has not sufficiently sensitive in high-risk women, as demonstrated by many series (11,25) and consequently, has a minor role in patients with hereditary predisposition to the disease. In fact, this diagnostic combination has demonstrated a sensitivity of 64% in our BRCA mutation carriers and a lower sensitivity than its estimated (83%) for detection in the general population, as well known from many studies (12,16,25,32,33). Furthermore, the higher sensitivity of MRI in lesion detection is consistent if considering its high capability to detect potential axillary nodal involvement.…”
Section: Discussionmentioning
confidence: 81%
“…17 From these imaging modalities, investigators evaluated the response to radiotherapy with regard to several underlying variables, including lesion size, 18,21,23 density, 6,14 -17,19,20 , metabolic tumor activity, 22 -24 and signal intensity. 25,26 Table 2 highlights the relationship between each of these underlying variables and the quantified metrics used to assess them.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies evaluated signal intensity response to palliative radiotherapy. 20,25,26 Measurements of signal intensity comprised T1TSE MRI signal intensity, apparent diffusion coefficient (ADC) values, and a combination of ADC values and b values.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of these effects results in a reduction in the bone mineral density (BMD) in patients undergoing pelvic RT (43). The incidence of IF seems to be higher than expected, although there are many discrepancies in the various study (5,(10)(11)(12)(13)(14)(44)(45)(46), probably due to the differences in the follow-up, as the choice of imaging may increase the detection of asymptomatic IFs. One study reported 89% of patients had findings compatible with IF after pelvic RT using magnetic resonance imaging (47), while another study reported 34% using bone scintigraphy (48).…”
Section: Discussionmentioning
confidence: 99%